2010
DOI: 10.1016/j.cmet.2010.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Development of Brown Adipocytes in the Murine and Human Adipose Organ

Abstract: Murine white and brown adipocytes are found together in dissectible visceral and subcutaneous fat depots supplied by specific vessels and nerves, forming a multi-depot organ with plastic properties. Many of the anatomo-physiological features of murine fat depots apply to humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
299
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 398 publications
(328 citation statements)
references
References 24 publications
(26 reference statements)
10
299
0
11
Order By: Relevance
“…First, BAT is present and metabolically active in adults [43,44] and is overactive in suicides associated with a depressive episode [45]. Second, once BAT has become metabolically active through temperature changes, it is more resistant to becoming quiescent [46] and may thereby contribute to the risk of suicide over a prolonged period.…”
Section: Discussionmentioning
confidence: 99%
“…First, BAT is present and metabolically active in adults [43,44] and is overactive in suicides associated with a depressive episode [45]. Second, once BAT has become metabolically active through temperature changes, it is more resistant to becoming quiescent [46] and may thereby contribute to the risk of suicide over a prolonged period.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, previous reports have demonstrated that mRNA expression of inflammatory genes was unaltered in buffalo humps in HIV-infected patients, 28 and expression of inflammatory genes was significantly lower in dorsocervical versus abdominal scAT in HIV-infected patients with lipodystrophy. 37 Recent studies have provided evidence for the presence of brown adipocytes in cervical fat from adult control subjects, characterized by numerous mitochondria expressing UCP1 (reviewed in Fontini and Cinti 38 ). In dorsocervical fat or buffalo humps in HIV-infected patients, conflicting results have been reported insofar as mtDNA content and UCP1 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…White and brown adipocytes display distinctive features by transmission electron microscopy (1,2,3). White adipocytes contain a single large lipid droplet occupying about 90% of the cell volume.…”
mentioning
confidence: 99%
“…In experimental animals, gross anatomy demonstrates that the adipose organ has a multi-depot organisation (1,2,3), consisting of two large subcutaneous depots and of numerous visceral depots (intended here as fat in close apposition to viscera, regardless of their portal or caval venous drainage) located in the visceral cavities of the trunk (Fig. 1).…”
mentioning
confidence: 99%